Waste clay from bauxite beneficiation to produce calcium sulphoaluminate eco-cements. (18th July 2022) - Negrão, Leonardo Boiadeiro Ayres; Costa, Marcondes Lima da; Pöllmann, Herbert
Highlights: The waste clay from beneficiation of bauxite ore has high alumina contents. The waste can be used to produce calcium sulphoaluminate eco-cements. 32% less CO2 is generated in their process production compared to traditional cements. Produced mortars developed higher strength compared to a Portland cement. Abstract: The beneficiation process of bauxite (Al-ore) generates over 10 mi tons of waste clay disposed of in tailing ponds. The purpose of this work was to test this material to produce CSA–based cements. Raw mixtures with the clay were formulated to maximize ye'elimite contents in the clinkers. A CSA-belite clinker composed of 46% of ye'elimite, 40% of belite, and minor amounts of Fe-perovskite and brownmillerite was produced. Cement pastes using clinker to gypsum ratios of 90:10, 85:15, and 75:25 developed compressive strength higher than a Portland cement. The pastes have major contents of ettringite and kuzelite depending on the sulfate additions, besides straetlingite, aluminium hydroxide and hemicarboaluminate. The waste clay is as a potential raw material for CSA-belite low-CO2 cements.